Дiя адрiамiцину на бiоенергетичнi процеси в тканинах печiнки та серця щурiв i ї ї корекцiя попередниками та модуляторами бiосинтезу убiхiнону - Кучменко, О.Б.; Петухов, Д.М.; Донченко, Г.В. (Видавничий дім "Академперіодика" НАН України, 2007)
The results of studies of the effect of complexes of precursors and modulators of coenzyme Q biosynthesis bioenergetical processes under adriamycin-induced cardiomyopathy are given. We show that adriamycin-induced cardiomyopathy is characterized by changes in bioenergetical processes, particularly in the coenzyme Q content and in the activity of complexes II and IV of the mitochondrial electron transport chain. Treatment of experimental animals with complexes of precursors and modulators of coenzyme Q biosynthesis normalizes the coenzyme Q content and the function of the mentioned enzyme complexes. Data presented may become a basement for the development of approaches to adriamycin cardiotoxicity correction.